Ordered and disordered cyclodextrin nanosponges with diverse physicochemical properties. Issue 38 (3rd May 2017) - Singh, Vikramjeet; Xu, Jianghui; Wu, Li; Liu, Botao; Guo, Tao; Guo, Zhen; York, Peter; Gref, Ruxandra; Zhang, Jiwen
Abstract : Herein, in addition to conventional β-CD-NSPs, the NSPs of α, γ, HP-β, methyl-β, and SBE-β cyclodextrins were synthesized by a simple modified approach and thoroughly characterized. Abstract : Herein, in addition to conventional β-CD-NSPs, the NSPs of α, γ, HP-β, methyl-β, and SBE-β cyclodextrins were synthesized by a simple modified approach and thoroughly characterized. The control of CDs derivatization over structural dimensions and properties was clearly observed. It is interesting to note the complete transformation of β-CD from its crystalline form to its non-crystalline derivatives and the further reversal when the derivatives are prepared into NSPs including those of α and γ-CDs (as observed by PXRD). The SEM images revealed the different morphologies and porous structure of NSPs and, in particular, the NSPs of methyl-β-CD exhibited regular spherical shapes. Two drugs of different categories, doxorubicin and captopril, were evaluated for loading efficiencies, which were found to significantly vary with cross-linker ratio (1 : 4 and 1 : 6) and CD types. Together, all the synthesized NSPs provide a new horizon to try to solve existing problems relating to drug delivery.